Mixed-flow pumps modeling, simulation, and measurements - Li, Wei; Ji, Leilei; Agarwal, Ramesh K. 1947-; Shi, Weidong; Zhou, Ling (Wiley-ASME Press series, 2024)
Mixed-flow PumpsModeling, Simulation, and MeasurementsLearn to improve and optimize the design and operation of mixed-flow pumpsMixed-flow pumps have a huge range of applications in agriculture, hydroelectric power, and other industries that incorporate fluid transport. They are centrifugal pumps incorporating the characteristics of both axial and radial pumps to increase the flow rate and discharge pressure. Though essential in a variety of industries, they pose serious challenges to numerical simulation methods, challenges which are starting to be met by the application of computational fluid dynamics using high-performance computing.Mixed-flow Pumps introduces engineers and researchers to this subject and its important applications. Incorporating all major varieties of mixed-flow pumps used in industrial applications, it employs methods from advanced computational fluid dynamics and high-precision flow field experimentation to characterize and analyze these crucial technologies. Moving from the fundamentals of the technology to its most advanced applications, it's an essential resource for engineers and industry practitioners looking to develop their understanding of fluid transport.Mixed-flow Pumps readers will also find:* Detailed information on how to design and optimize mixed-flow pumps to meet the increasingly stringent industry demands* Detailed information on energy performance tests and experiments, methods for data analysis, entropy production theory, CFD solutions using Reynolds-Averaged Navier-Stokes (RANS) equations, and more* An authoritative team with immense global experience in flow pumps and broader industrial experienceMixed-flow Pumps is a useful reference for mixed-flow pump design by academic researchers, including graduate students, industry practitioners, and test engineers